Interplay of structural fluctuations and charge carrier dynamics is key for high performance of hybrid lead halide perovskites. Issue 21 (12th September 2022) - Zhan, Juan; Yang, Jack; Xie, Xiaoyin; Prezhdo, Oleg V.; Li, Wei
Abstract : Interplay of organic cation rotation and inorganic lattice fluctuation maintains the high performance of hybrid organic–inorganic perovskites. Abstract : The ability of methylammonium lead triiodide (MAPbI3 ) to achieve photoelectric conversion efficiency that is on par with crystalline silicon has led to a surge of interest in perovskite photovoltaics. However, an in-depth understanding of how the ubiquitous coupling between the fast rovibrational movements of the organic cations and the phonon vibrations of the inorganic framework affects the relaxation and recombination of hot carriers remains largely elusive. Access to such knowledge is critical to guide design and increase efficiency of new classes of perovskite solar cells. We report a time-domain ab initio investigation of temperature dependent excited state dynamics in MAPbI3, with particular emphasis on nuclear anharmonic effects. The observed strong anharmonicity is attributed to softness of the material and unusual dynamical coupling between the organic and inorganic components. At an elevated temperature, the hydrogen bonding between MA and iodines is weakened, enhancing rotation of MA cations, which become more dynamically disordered. As a result, thermal vibrations of the inorganic Pb–I sublattice are suppressed, and the lattice anharmonicity is decreased. Thermal fluctuations of the electronic energy levels are found to follow the trend of anharmonic motions of Pb and I atoms, with holes relaxing faster to the band edges than electrons, due to higher density of the hole states. While elevated temperature accelerates intraband carrier cooling, it slows nonradiative carrier recombination. The latter result is important for performance, since solar cells and other devices heat up during operation. The reported signatures of coupled structural dynamics of the organic cations and inorganic framework unravel the interplay between anomalous structural fluctuations and charge carrier dynamics, which is of particular importance for fundamental understanding of the structure–property relationships in hybrid metal halide perovskites.